2018
DOI: 10.1371/journal.pone.0198286
|View full text |Cite
|
Sign up to set email alerts
|

Learning to live with ticks? The role of exposure and risk perceptions in protective behaviour against tick-borne diseases

Abstract: The purpose of this study is to analyse the role of risk perceptions and exposure for protective behaviour against tick bites and the related diseases Lyme borreliosis (LB) and tick-borne encephalitis (TBE), both of which are growing health concerns. We use data from a national survey in Sweden with respondents in geographical areas with substantial differences in both abundance of ticks and incidence of LB and TBE. We find that the share of respondents who frequently use protective clothing (64%), perform tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 52 publications
10
50
1
2
Order By: Relevance
“…Interestingly, while some previous reports have inquired KAP of medical professionals on other tick-borne disorders (e.g., Lyme disease) [ 29 , 30 , 31 ], there is a significant lack of evidence on OP and their understanding of TBE [ 7 , 14 , 15 , 16 , 32 ]. Some studies that have examined acceptance of preventive measures in endemic areas found uneven or low use of risk-reducing measures, suggesting that people at risk either ignore or underestimate the health threat from TBE, being unaware of risks and protective measures, or do not understand that the adoption of protective measures is worth their time [ 14 , 15 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, while some previous reports have inquired KAP of medical professionals on other tick-borne disorders (e.g., Lyme disease) [ 29 , 30 , 31 ], there is a significant lack of evidence on OP and their understanding of TBE [ 7 , 14 , 15 , 16 , 32 ]. Some studies that have examined acceptance of preventive measures in endemic areas found uneven or low use of risk-reducing measures, suggesting that people at risk either ignore or underestimate the health threat from TBE, being unaware of risks and protective measures, or do not understand that the adoption of protective measures is worth their time [ 14 , 15 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, a previous report from North-Eastern Italy pointed out that a high percentage of farmers usually avoid behavioral protective and preventive measures [ 14 , 33 , 35 ]. Despite half of participants recalled tick bites while performing their work tasks [ 14 ], the systematic body checks for tick bites after field work (i.e., 2.8%) was often not performed [ 33 , 36 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearing light-colored clothes is beneficial as it makes ticks easier to detect and remove before they have the opportunity to attach. Long pants tucked into socks and wearing non-open shoes can reduce contact with ticks [56,59].…”
Section: Personal Protective Measuresmentioning
confidence: 99%
“…Due to climate change, ticks have recently been colonizing new areas (Jaenson et al 2012, Ragagli et al 2016, Tarageľová et al 2016 and so the incidence of tick-borne diseases has increased in such areas. Beside using protective clothing and tucking trousers into socks, the use of repellent represents the only possible protection against tick attachment (Slunge and Boman 2018).…”
Section: Introductionmentioning
confidence: 99%